THE EFFECT OF PROBIOTIC Lactobacillus acidophilus AND Bifidobacterium sp ON FEED CONSUMPTION AND HEN DAY PRODUCTION (HDP) LAYING OF INFECTED Escherichia coli - Huda, Khoirul (Universitas Djuanda Bogor, 2019)
The purpose of this study was to determine the use of probiotics Lactobacillus acidophilus and Bifidobacterium sp on feed consumption and Hen Day Production (HDP), layer was infected with Escherichia coli. About 120 layers at 25 weeks of age were randomized into six treatments. The treatment consisted of factors a (infection and non-infection Escherichia coli) and factor b (basal feed, AGP and probiotics). The results of the study gave probiotics an effect (p <0.05) on feed consumption and HDP. The highest feed consumption was found in the treatment of infectious probiotics is 114,7g and the highest HDP was treated with non-infectious probiotics is 98,6%. Infection factors have an effect (p <0.05) on HDP but have no effect (p> 0.05) on feed consumption. There was interaction between probiotic and infection factors (p <0.05) on HDP but there was no interaction (p> 0.05) between probiotic and infection factors on feed consumption. It could be concluded that the administration of probiotics can produce good production performance and high profitsKeywords: Production, infection, probiotic, interactions